Mutational analysis of Mdm2 C-terminal tail suggests an evolutionarily conserved role of its length in Mdm2 activity toward p53 and indicates structural differences between Mdm2 homodimers and Mdm2/MdmX heterodimers - Dolezelova, Pavlina; Cetkovska, Katerina; Vousden, Karen H; Uldrijan, Stjepan (Cell cycle (Georgetown, Tex.), 2012)
Mdm2 can mediate p53 ubiquitylation and degradation either in the form of the Mdm2 homodimer or Mdm2/MdmX heterodimer. The ubiquitin ligase activity of these complexes resides mainly in their respective RING finger domains and also requires adjacent C-terminal tails. So far, structural studies have failed to show significant differences between Mdm2 RING homodimers and Mdm2/MdmX RING heterodimers. Here, we report that not only the primary amino acid sequence, but also the length of the C-terminal tail of Mdm2 is highly conserved through evolution and plays an important role in Mdm2 activity toward p53. Mdm2 mutants with extended C termini do not ubiquitylate p53 despite being capable of forming Mdm2 homodimers through both RING-acidic domain and RING-RING interactions. All extended mutants also retained the ability to interact with MdmX, and this interaction led to reactivation of their E3 ubiquitin ligase activity. In contrast, only a subset of extended Mdm2 mutants was activated by the interaction with Mdm2 RING domain, suggesting that Mdm2 homodimers and Mdm2/MdmX heterodimers may not be structurally and functionally fully equivalent.
Keywords: molekulární evoluce; nádorový supresorový protein p53; Molecular Sequence Data; Protein Structure, Tertiary; nádorové buněčné linie; sekvence aminokyselin; Dimerization; Protein Binding; HEK293 Cells; DNA Mutational Analysis; dimerizace; protoonkogenní proteiny c-mdm2; Tumor Suppressor Protein p53; Cell Line, Tumor; mutační analýza DNA; Proto-Oncogene Proteins c-mdm2; inhibitory apoptózy; HEK293 buňky; Humans; Amino Acid Sequence; vazba proteinů; molekulární sekvence - údaje; Inhibitor of Apoptosis Proteins; terciární struktura proteinů; lidé; Evolution, Molecular